IMPLEMENTASI KELULUSAN MAHASISWA BERDASARKAN DATA NILAI AKADEMIK MENGGUNAKAN ALGORITMA DECISION TREE - Wildatul Hasanah; Zaehol Fatah (CV. Denasya Smart Publisher, 2024)
Predicting student graduation is one of the important things in managing education in higher education. By using academic score data such as course grades and Grade Point Average (GPA),Can predict student graduation more efficiently. This article implements the Decision Tree algorithm to predict student graduation based on their academic score data. The Decision Tree algorithm has proven to be effective in making predictions based on existing attributes. The research results show that this model has good accuracy in predicting student graduation status.